Meeting Globalization's Challenges : Policies to Make Trade Work for All - Lagarde, Christine, 1956-; Obstfeld, Maurice; Catão, Luis (Book collections on Project MUSE., 2019)
"In the US, in Europe, and throughout the world, globalization, in tandem with technological progress, has left a massive number of people behind, feeling dispossessed, disenfranchised, and angry. Leading the charge of "hyperglobalization" during the second half of the last century, and enforcing the Western framework of austerity in the developing world has been the International Monetary Fund. Along with the World Bank and WTO, many consider the IMF one of the most consequential institutions to have pushed the world economy blindly towards excessive globalization, while not adequately considering its powerful negative consequences. In October 2017, however, the IMF convened with some of the world's most celebrated economists and experts on trade and globalization to have an honest discussion on the most pressing concerns the world faces today as a result of globalization, and how to address the extensive challenges it has created. Edited by chief economist Maurice Obstfeld and senior economist Luis Catao of the IMF, the book brings together a team of respected senior economists with the most promising younger scholars to address five major themes: how globalization affects economic growth and social welfare; potential political implications of an honest discussion of globalization, and that "free trade may not be politically viable"; free trade's role in global inequality; how workers adjust or not when they're dislocated by globalization; and how trade policy influences the way countries develop their economies and societies. The book could represent a historic milestone at which the world's top economists and policymakers have an unprecedented, honest debate about the real costs and consequences of globalization"--